Mobile waste and recycling containers. Containers with 4 wheels with a capacity up to 1 700 l with flat lid(s), for wide trunnion or BG- and/or wide comb lifting devices. Dimensions and design Part 4, (17th April 2020) - British Standards Institution,
No abstract available